In vivo efficacy of artemether-lumefantrine and artesunate-amodiaquine for uncomplicated Plasmodium falciparum malaria in Malawi, 2014. (December 2016) - Paczkowski, Magdalena; Mwandama, Dyson; Marthey, Daniel; Luka, Madalitso; Makuta, Georgina; Sande, John; Ali, Doreen; Troell, Peter; Mathanga, Don; Gutman, Julie
Abstract Background Malaria causes significant morbidity in Malawi, with an estimated 5 million cases in 2014. Artemether-lumefantrine (AL) and artesunate-amodiaquine (ASAQ) are the first- and second-line treatments for uncomplicated malaria, respectively, but emerging resistance threatens their efficacy. In order to understand whether AL and ASAQ remain efficacious for the treatment of uncomplicatedPlasmodium falciparum malaria in Malawi, a therapeutic efficacy trial was conducted. Methods During March–July 2014, febrile children aged 6–59 months with microscopy-confirmed uncomplicatedP. falciparum malaria (1000–200, 000 parasites/μL) were enrolled in a 28-day randomized in vivo efficacy trial at three sites: one each in northern (Karonga), central (Nkhotakota) and southern (Machinga) Malawi. The study was powered to estimate site-specific efficacy for AL and overall efficacy for ASAQ, with 3:1 randomization to AL or ASAQ. Blood was collected for malaria microscopy and molecular testing on days 0–3, 7, 14, 21, and 28. Recrudescence and reinfection were differentiated using polymerase chain reaction (PCR) genotyping of merozoite surface protein. The primary outcome was the PCR-corrected day 28 Kaplan–Meier cumulative success rate. Results A total of 452 children were enrolled; 303/338 (89 %) and 98/114 (86 %) reached a study endpoint in AL and ASAQ arms, respectively. All treatment failures occurred after day 3. The day 28 uncorrected cumulative success rate was 97.1 % (95 % confidence interval [CI]: 93.9–100 %) for ASAQ and 76.8 % (95 % CI 72.1–81.5 %) for AL, with 82.5 % (95 % CI 75.4–89.7 %), 69 % (95 % CI 59.9–78.1 %), and 78.2 % (95 % CI 70.2–86.3 %) success in the northern, central, and southern regions, respectively. The day 28 PCR-corrected cumulative success rate was 99 % (95 % CI 97.2–100 %) in the ASAQ arm and 99.3 % (95 % CI 98.3–100 %) in the AL arm, with 98–100 % efficacy in each site. Conclusions As evidenced by the day 28 PCR-corrected cumulative success rates, both AL and ASAQ remain efficacious treatments for uncomplicated malaria in Malawi. The lower uncorrected efficacy in the AL arm compared to ASAQ may be explained by the shorter half-life of lumefantrine (3–6 days) compared to amodiaquine (9–18 days). The high reinfection rate suggests that there is a continued need to scale-up effective malaria prevention interventions.